INTEGRATING ISLAMIC CULTURAL VALUES IN MATHEMATICS: A HISTORICAL REFLECTION ON THE ISLAMIC GOLDEN AGE - Kurniawan, Wakib; Ayuningsih, Resti Fatma; Al Ayyubi, Ibnu Imam; Putra, Ari Limay Trisno; binti Ab Rahman, Siti Fatinnah (Jazirah: Jurnal Peradaban dan Kebudayaan, 2025)
This study examines the implementation of Islamic cultural values in the development of mathematics during the Islamic Golden Age (8th to 13th centuries CE). A historical approach is employed to explore the contributions of Muslim scholars such as Al-Khawarizmi, Al-Battani, and Umar Khayyam in formulating mathematical theories that laid the foundation for modern science. The findings of the research indicate that Islamic cultural values, such as Tawhid (monotheism), Ijtihad (independent reasoning), balance, and responsibility, spurred the emergence of innovations and scientific ideas with universal significance. Institutions like Bayt al-Hikmah became centers of research that integrated spiritual values with the exploration of knowledge. Through these values, mathematics became not only a technical discipline but also one with profound philosophical meaning. This study emphasizes that the integration of Islamic cultural values in science significantly contributed to the advancement of Islamic civilization and the intellectual heritage of the world.